Association of triglyceride-glucose related indices with mortality among individuals with MASLD combined with prediabetes or diabetes - Yiheng Zhang; Juanli Wu; Tao Li; Yundong Qu; Yan Wang (Cardiovascular Diabetology)
Abstract Background The prognostic significance of triglyceride-glucose (TyG)-related indices in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD) combined with prediabetes or diabetes is not yet fully understood. In this study, we explored their predictive value for mortality in this specific population. Methods Patients with MASLD were identified from the National Health and Nutrition Examination Survey (NHANES III) database. TyG and its related parameters [TyG-waist circumference (TyG-WC), TyG-waist-to-height ratio (TyG-WHtR), TyG-weight-adjusted waist index (TyG-WWI), and TyG-body mass index (TyG-BMI), ] were calculated. To examine the association between TyG-related indices and mortality risk, Cox regression models were utilized. Furthermore, we employed restricted cubic spline (RCS) analysis to investigate potential dose-response relationships. The predictive ability of the TyG indices for mortality was assessed by analyzing the time-dependent area under the curve (AUC). Results In the cohort of patients with prediabetes or diabetes, 46.5% were diagnosed with MASLD. Over a median follow-up of 25.4 years, 1,163 individuals (53.9%) died, with 329 (15.3%) deaths attributed to cardiovascular causes and 78 (3.6%) to diabetes. Multivariate Cox regression models showed that TyG, TyG-BMI, TyG-WHtR, TyG-WWI, and TyG-WC were associated with all-cause and cardiovascular/diabetes-specific mortality. Furthermore, RCS analysis revealed a positive linear relationship between the TyG and TyG-WWI indices and all-cause mortality (p for nonlinear = 0.920; p = 0.525, respectively). In contrast, the TyG-WC, TyG-BMI, and TyG-WHtR indices exhibited a positive nonlinear association with all-cause mortality (p for nonlinear = 0.001; = 0.003; = 0.007, respectively). Time-dependent AUC curves demonstrated that the TyG-WWI index was the most robust predictor of both all-cause and cardiovascular mortality. Conclusions Elevated levels of TyG, TyG-BMI, TyG-WHtR, TyG-WWI, and TyG-WC indices were associated with a poorer prognosis in MASLD patients with prediabetes or diabetes, with TyG-WWI being the strongest predictor.